Global Volume Distribution for Subaerial Volcanism on Earth. Issue 6 (4th June 2021) - Papale, P.; Marzocchi, W.; Garg, D.
Abstract: Knowledge of the global distribution of Earth volcanism is critical in many fields of the Geosciences involving large‐scale assessments, such as plate tectonics, global volcanic hazards, and climate change. Recent analysis has revealed that global eruption inter‐event times are exponentially distributed, implying that on the global scale volcanic eruptions are Poisson distributed. Here, we employ those findings to calibrate a continuous frequency‐volume distribution for subaerial eruptions of any size on Earth from small lava flows to super‐eruptions. Obtaining such a continuous global distribution implies considering the existing data and the way they are collected and categorized into databases, as well as extending the available eruption volume data to eruption VEI classes less than 4. The continuous global distribution shows an initial log‐normal section up to volumes of about 170 Mm 3, followed by a power‐law section, tapered on its extreme right‐end side, encompassing about five orders of magnitude of eruption volumes. The potential implications are discussed in terms of short‐term eruption forecasts of the size of an impending eruption, critical for volcanic emergency management. Plain Language Summary: The occurrence of volcanic eruptions over the Earth follows apparently complex patterns: while the vast majority of the eruptions are relatively small in size, here and there less frequent large eruptions appear, and even less frequently, cataclysmic eruptions take place menacing vast regions up to the global Earth. Summed up with relatively quick deterioration of the information from the geologic record, especially for small to medium size eruptions, such apparently irregular trends have largely limited our understanding and forecasting capabilities. New databases of volcanic eruptions, and new statistical analyses, allow us to determine the size distribution of volcanic eruptions worldwide, from the smallest lava flows to the largest explosive eruptions known to have occurred on Earth. We find that above a relatively small eruption volume threshold all eruptions distribute according to what is called a power law, which is also known to describe other natural phenomena such as earthquakes, wild fires, and many others. The mechanisms subtending the generation of a power‐law distribution for the global subaerial volcanism are not immediately clear. However, as for several other similarly distributed phenomena, the implications may impact our capability to forecast the size of an impending eruption, with relevant consequences for volcanic emergency management. Key Points: The continuous distribution of global subaerial volcanism on Earth is modeled and quantified The distribution displays an initial (erupted volume < 170 Mm 3 ) log‐normal section, followed by a power law section encompassing several orders of magnitude Power law—distributed eruption volumes may rule out the possibility of short‐term deterministic forecasts of the size of an impending eruption